2014
DOI: 10.1098/rsif.2013.0818
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanoscale surface curvature on the oligomerization of surface-bound proteins

Abstract: ReviewCite this article: Kurylowicz M, Paulin H, Mogyoros J, Giuliani M, Dutcher JR. 2014 The effect of nanoscale surface curvature on the oligomerization of surface-bound proteins. J. R. Soc. The influence of surface topography on protein conformation and association is used routinely in biological cells to orchestrate and coordinate biomolecular events. In the laboratory, controlling the surface curvature at the nanoscale offers new possibilities for manipulating protein-protein interactions and protein fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 82 publications
1
37
0
Order By: Relevance
“…36 The topography and curvature on the particle surface may also play a role in determining the interactions of the adsorbed guests as reported for other particle–protein systems (e.g., albumin, fibrinogen). 35,38 …”
Section: Resultsmentioning
confidence: 99%
“…36 The topography and curvature on the particle surface may also play a role in determining the interactions of the adsorbed guests as reported for other particle–protein systems (e.g., albumin, fibrinogen). 35,38 …”
Section: Resultsmentioning
confidence: 99%
“…When the surfaces are under high shear, less protein adsorption occurs. Further, Kurylowicz et al [135] showed that as surface curvature increased, the number of protein dimers and higher order aggregates decreased. The authors use polystyrene (PS) surfaces, either flat or with adsorbed nanoparticles that are 50 or 27 nm in diameter, and employ single-molecule force microscopy to show that lactalbumin and lactoglobulin are more closely packed on the flat than highly curved surfaces.…”
Section: Protein Adsorption To Superhydrophobic Biomaterialsmentioning
confidence: 99%
“…167 As the surface curvature (k) of a sphere can be defined simply as a reciprocal to the radius (R), k = 1/R, 177 a decrease in particle size would therefore translate to a significant increase in the local curvature. 179 Along the same line, the manner in which the proteins adsorb, arrange and pack on the nanomaterials surface will therefore be highly dependent on the nanomaterials surface curvature. 178 When a protein approaches a NM with a diameter that is so much bigger than the size of the protein, what the protein 'perceives' is essentially a flat surface.…”
Section: Ecs Heterogeneity In Diseased Vascular Bedsmentioning
confidence: 99%